Proton exchange membranes based on heterocycles and acids through an organic-inorganic hybrid process - ZHOU ZHEN; LIU MEILIN; ZHU XIAOBING (2013)
Polymer electrolyte membranes (PEMs), methods and use thereof in fuel cells and methods of preparing thereof are disclosed. A PEM may include at least one porous support film and a polysiloxane polymer bonded to the at least one porous support film, wherein the polysiloxane polymer includes at least one polysiloxane grafted to a heterocycle.